Kegiatan Usaha Bank Syariah dan Perbedaannya Dengan Konvensional - Kartika, Meri; Andrini, Rozi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Islamic banks play a strategic role in providing financial services that comply with Islamic principles. Their business activities include mobilizing and channeling funds through various contracts, as well as developing innovative financial products. The primary difference between Islamic and conventional banks lies in the underlying principles of their operations. While conventional banks focus on financial returns, Islamic banks emphasize justice, sustainability, and social responsibility. The business activities of Islamic banks aim not only to generate profit but also to contribute to sustainable economic development. By providing inclusive financial access, Islamic banks play a crucial role in empowering communities, particularly in the micro, small, and medium enterprises (MSMEs) sector. This research aims to explore the role of Islamic banks in the Indonesian economy and their comparison with conventional banks.